2016
DOI: 10.1080/2162402x.2015.1106677
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of tumor-associated macrophages in colorectal cancer: Impact on single cell invasion (tumor budding) and clinicopathological outcome

Abstract: Tumor-associated macrophages (TAM) play a controversial role in epithelial-mesenchymal transition (EMT) and prognosis of colorectal cancer (CRC). In particular, the microlocalization, polarization and prognostic impact of TAM in the immediate environment of invading CRC cells has not yet been established. To address this clinically relevant question, intraepithelial (iCD68) and stromal macrophages (sCD68), M1-macrophages (iNOS), M2-macrophages (CD163), cytokeratin-positive cancer cells (tumor buds) and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 35 publications
3
116
1
1
Order By: Relevance
“…Surprisingly, heavy CD163 + M2 macrophage infiltration in CRC tumors was found in tumors of a lower grade and in patients with fewer lymph node metastases. A survival benefit was seen in patients with high CD163 + M2 macrophages, but not with iNOS + macrophages [11]. In addition, in a study with 158 CRC patients with liver metastases suggested that high TAMs infiltration in primary tumors is correlated with a better clinical outcome [12].…”
Section: Dual Role Of Tams In Crcmentioning
confidence: 99%
“…Surprisingly, heavy CD163 + M2 macrophage infiltration in CRC tumors was found in tumors of a lower grade and in patients with fewer lymph node metastases. A survival benefit was seen in patients with high CD163 + M2 macrophages, but not with iNOS + macrophages [11]. In addition, in a study with 158 CRC patients with liver metastases suggested that high TAMs infiltration in primary tumors is correlated with a better clinical outcome [12].…”
Section: Dual Role Of Tams In Crcmentioning
confidence: 99%
“…In fact, the modulation of their activity seems to be localized within the tumor mass. TAMs at the tumor edges induce apoptosis in cancer cells, while TAMs localizing at the invasive front showed a resistant phenotype to suppressive TME (64,65). Recent studies highlight that TAM plasticity, modulated by different microenvironmental factors, has a prognostic impact on CRC patients (64,65).…”
Section: Immune Cellsmentioning
confidence: 99%
“…TAMs at the tumor edges induce apoptosis in cancer cells, while TAMs localizing at the invasive front showed a resistant phenotype to suppressive TME (64,65). Recent studies highlight that TAM plasticity, modulated by different microenvironmental factors, has a prognostic impact on CRC patients (64,65). An integrative study, proposed by Mlecnik et al showed that among the heterogeneous group of CRC patients with a mismatch repair-deficient and microsatellite instability-high (MSI-H) phenotype, two groups can be distinguished: the most represented group with high T-cell activity and improved prognosis, and a minor group with reduced T-cell activity and poor prognosis (66).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Although the use of H&E for TB counting is feasible in most cases, TB identification may be difficult in tumours with inflammatory infiltrate and/or striking fibrosis with reactive stromal cells. For these reasons, some authors favour the use of cytokeratin (CK) immunostaining to improve the visualisation of tumour buds and reproducibility of the assessment . Moreover, counting in such a limited area may result in overclassification of cases with focal TB activity that may not have the same aggressive potential as cases with diffuse and intense budding .…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, some authors favour the use of cytokeratin (CK) immunostaining to improve the visualisation of tumour buds and reproducibility of the assessment. [13][14][15] Moreover, counting in such a limited area may result in overclassification of cases with focal TB activity that may not have the same aggressive potential as cases with diffuse and intense budding. [16][17][18] In this study, we aimed to improve the accuracy and reproducibility of the recommended TB evaluation method by CK immunostaining, increasing the number of counted fields, and assessing cell proliferation, the apoptotic index and the emperipoletic index in tumour buds.…”
Section: Introductionmentioning
confidence: 99%